Is Impaired Control of Reactive Stepping Related to Falls During Inpatient Stroke Rehabilitation?. (July 2013) - Mansfield, Avril; Inness, Elizabeth L.; Wong, Jennifer S.; Fraser, Julia E.; McIlroy, William E.
Background . Individuals with stroke fall more often than age-matched controls. Although many focus on the multifactorial nature of falls, the fundamental problem is likely the ability for an individual to generate reactions to recover from a loss of balance. Stepping reactions to recover balance are particularly important to balance recovery, and individuals with stroke have difficulty executing these responses to prevent a fall following a loss of balance. Objective . The purpose of this study is to determine if characteristics of balance recovery steps are related to falls during inpatient stroke rehabilitation. Methods . We conducted a retrospective review of individuals with stroke attending inpatient rehabilitation (n = 136). Details of falls experienced during inpatient rehabilitation were obtained from incident reports, nursing notes, and patient interviews. Stepping reactions were evoked using a "release-from-lean" postural perturbation. Poisson regression was used to determine characteristics of stepping reactions that were related to increased fall frequency relative to length of stay. Results . In all, 20 individuals experienced 29 falls during inpatient rehabilitation. The characteristics of stepping reactions significantly related to increased fall rates were increased frequency of external assistance to prevent a fall to the floor, increased frequency of no-step responses, increased frequency of step responses with inadequate foot clearance, and delayed time to initiate stepping responses. Conclusions . Impaired control of balance recovery steps is related to increased fall rates during inpatient stroke rehabilitation. This study informs the specific features of stepping reactions that can be targeted with physiotherapy intervention during inpatient rehabilitation to improve dynamic stability control and potentially prevent falls.